Lower Respiratory Tract Infection in a Renal Transplant Recipient: Do not Forget Metapneumovirus. (14th November 2012) - Noel, N.; Rammaert, B.; Zuber, J.; Sayre, N.; Mamzer-Bruneel, M. F.; Leruez-Ville, M.; Mascard, L.; Lecuit, M.; Lortholary, O.
Abstract : Human metapneumovirus (h MPV ) is emerging as a cause of a severe respiratory tract infection in immunocompromised patients. h MPV pneumonia has only been seldom reported in nonpulmonary solid organ transplanted patients, such as renal transplant recipients. We report here a case of a 39-year-old patient presenting with fever, cough, and interstitial opacities on CT scan diagnosed as a nonsevere h MPV pneumonia 11 years after a renal transplantation. Infection resolved spontaneously. Differential diagnosis with Pneumocystis pneumonia was discussed. We review the medical literature and discuss clinical presentation and detection methods that can be proposed in solid organ transplant recipients.